2014
DOI: 10.1159/000365788
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Bone Metastases in Urologic Malignancies

Abstract: The skeletal system is the most common site of metastatic cancer spread. Bone metastases are often associated with severe morbidity, pain and functional impairment. Timely diagnosis and proper treatment may decrease morbidity, improve quality of life and in some cases even improve survival. External beam radiotherapy may effectively give pain relief in patients with painful bone metastases. In bone metastases from castration-resistant prostate cancer or urothelial bladder cancer, treatment with zoledronic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 29 publications
0
9
0
9
Order By: Relevance
“…mCRPC is yet one of the most diagnosed malignant diseases and remains the second-leading cause of tumour-associated deaths in male in the Western hemisphere [4]. Depending on local tumor progress and the presence of lymph node and bone metastasis, overall survival of mCRPC averaged 1.5 years during the last 2 decades [5,6]. Before 2010, docetaxel was the only available substance, which improved overall survival [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…mCRPC is yet one of the most diagnosed malignant diseases and remains the second-leading cause of tumour-associated deaths in male in the Western hemisphere [4]. Depending on local tumor progress and the presence of lymph node and bone metastasis, overall survival of mCRPC averaged 1.5 years during the last 2 decades [5,6]. Before 2010, docetaxel was the only available substance, which improved overall survival [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…About 20-25% of newly diagnosed BCas are muscle-invasive, and 5-10% are metastatic by the first manifestation. Bone is one of the most common sites of BCa metastases, and up to 27% of muscle-invasive TCCs present with bone metastases [13,14]. Early treatment is crucial for invasive BCa; studies have shown that delayed cystectomy can decrease survival rates for more than 3 months [6].…”
Section: Discussionmentioning
confidence: 99%
“…The patients were managed according to the following treatment strategies: patients without distant metastasis were treated with RNU with or without regional LN dissection (LND) in accordance with the previous report [25], patients with locally advanced disease or clinical LN metastasis were treated with radical surgery including extended LND according to the PET/CT findings with or without neoadjuvant chemotherapy, and patients with visceral metastasis or recurrent disease received palliative chemotherapy, radiotherapy, and/or palliative care [26]. All the patients gave informed consent to participate in this protocol.…”
Section: Methodsmentioning
confidence: 99%